A case of esophageal adenocarcinoma on long‐term rapamycin monotherapy. (19th May 2015) - Canha, Catarina; Ferreira, Raquel; Rovira, Jordi; Moya‐Rull, Daniel; Castells, Antoni; Diekmann, Fritz; Oppenheimer, Federico; Campistol, Josep Maria; Revuelta, Ignacio
Summary Cancer in transplant recipients represents a therapeutic challenge even when the patient is already under mTOR inhibitors. A 78‐year‐old man received a deceased donor kidney transplant in 1993. After 6 months, he developed a multifocal cutaneous and nonvisceral Kaposi's Sarcoma while on cyclosporine immunosuppressant therapy. The patient was converted to sirolimus monotherapy in 2001 with subsequent complete recovery within 2 years. In 2007, the patient was diagnosed with an esophageal adenocarcinoma stage IIA. An esophagectomy was performed without requirement of further treatment. He has continued on sirolimus monotherapy ever since, with no other incidents and no recurrences of either tumor. In this report, we describe an interesting case of a second cancer while on immunosuppressive therapy with anticancer activity. Moreover, the present knowledge of the matter is discussed.